Religiosity, Digital Marketing And Decision To Become A Bank Syariah Indonesia Customer: Motivation As Moderation - Ikhwan, Deviana Ardiani; Adha, Mufti Alam; Pambudi, Dwi Santosa (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the influence of religiosity and digital marketing on Generation Z's decision to become customers of Bank Syariah Indonesia, with motivation as a moderating variable. This quantitative study uses primary data in the form of questionnaires. The population of this study is Generation Z in Magelang, which has become a customer of Bank Syariah Indonesia, where the number is unknown. The sampling technique used random sampling with Lemeshow measurements, so 110 respondents were obtained. The data analysis technique used multiple linear and moderating regression analyses (MRA). The results of this study indicate that religiosity and digital marketing positively affect Generation Z's decision to become customers of Bank Syariah Indonesia. Motivation cannot moderate the influence of religiosity and digital marketing on Generation Z's decision to become customers of Bank Syariah Indonesia. Theoretically, this study can complement the theory regarding the influence of religiosity and digital marketing on decisions. This study can then be used as a reference for further research. Practically, the results of this study can be a reference for Islamic banking in increasing understanding of the behavior of Generation Z's decision to become customers of Islamic banks.